Exoantigens of Paracoccidioides spp. Promote Proliferation and Modulation of Human and Mouse Pulmonary Fibroblasts - Almeida Donanzam, Débora de Fátima; Donato, Tatiani Ayako Goto; Reis, Karoline Haghata dos; Silva, Adriely Primo da; Finato, Angela Carolina; Santos, Amanda Ribeiro dos; Cavalcante, Ricardo Souza; Mendes, Rinaldo Poncio; Venturini, James (Frontiers in Cellular and Infection Microbiology, 2020)
Paracoccidioidomycosis (PCM) is a systemic granulomatous fungal infection caused by thermally dimorphic fungi of the genus Paracoccidioides. Endemic in Latin America, PCM presents with high incidence in Brazil, Colombia, and Venezuela, especially among rural workers. The main clinical types are acute/subacute (AF) form and chronic form (CF). Even after effective antifungal treatment, patients with CF usually present sequelae, such as pulmonary fibrosis. In general, pulmonary fibrosis is associated with dysregulation wound healing and abnormal fibroblast activation. Although fibrogenesis is recognized as an early process in PCM, its mechanisms remain unknown. In the current study, we addressed the role of Paracoccidioides spp. exoantigens in pulmonary fibroblast proliferation and responsiveness. Human pulmonary fibroblasts (MRC-5) and pulmonary fibroblasts isolated from BALB/c mice were cultivated with 2.5, 5, 10, 100, and 250 µg/ml of exoantigens produced from P. brasiliensis (Pb18 and Pb326) and P. lutzii (Pb01, Pb8334, and Pb66) isolates. Purified gp43, the immunodominant protein of P. brasiliensis exoantigens, was also evaluated at concentrations of 5 and 10 µg/ml. After 24 h, proliferation and production of cytokines and growth factors by pulmonary fibroblasts were evaluated. Each exoantigen concentration promoted a different level of interference of the pulmonary fibroblasts. In general, exoantigens induced significant proliferation of both murine and human pulmonary fibroblasts (p < 0.05). All concentrations of exoantigens promoted decreased levels of IL-6 (p < 0.05) and VEGF (p < 0.05) in murine fibroblasts. Interestingly, decreased levels of bFGF (p < 0.05) and increased levels of TGF-β1 (p < 0.05) and pro-collagen I (p < 0.05) were observed in human fibroblasts. The gp43 protein induced increased TGF-β1 production by human cells (p = 0.02). In conclusion, our findings showed for the first time that components of P. brasiliensis and P. lutzii interfered in fibrogenesis by directly acting on the biology of pulmonary fibroblasts.